Upaya Orang Tua Dalam Meningkatkan Self Confidence Anak Berkebutuhan Khusus Autisme - Destiva Trisna; Winda Oktaviana; Suci Pramugari (Departement of Mathematics Education, 2024)
In developing the self-confidence of children with autism, the role of parents is crucial. It involves not only providing love and support but also demonstrating perseverance in accompanying and motivating them. This research aims to strengthen the self-confidence of children with autism, focusing on the often disrupted aspects of communication and socialization. Through their roles as guides, facilitators, and motivators, parents can help these children achieve better mental balance, particularly in enhancing self-confidence. The research method employed is qualitative, utilizing the literature study method. A literature study involves activities related to collecting literature data, reading and taking notes, as well as managing research materials. The data collection technique used is theoretical review, gathering information from books, websites, journals, scholarly works, and other sources.The results of the research indicate that the role of parents as guides, facilitators, and motivators is highly significant. They can create a supportive environment for children with autism, reinforcing their self-confidence through positive interactions and sustained encouragement. However, parents also face internal and external challenges that can affect the development of self-confidence in children with autism.